Multifunctional nanoparticles as a tissue adhesive and an injectable marker for image-guided procedures - Kwangsoo Shin; Jin Woo Choi; Giho Ko; Seungmin Baik; Dokyoon Kim; Ok Kyu Park; Kyoungbun Lee; Hye Rim Cho; Sang Ihn Han; Soo Hong Lee; Dong Jun Lee; Nohyun Lee; et al. (Nature Communications, 2017)
The use of tissue adhesives for the closure of wounds is of growing interest for surgery and trauma management. Here, the authors develop an adhesive that is biocompatible, enables tissue adhesion and also permits real-time imaging due to the presence of contrast agents for multiple modalities.